Comparison Of Income From Organic Rice And Non-Organic Farming In Dukuh Village, Delanggu District, Klaten Regency - Primaningsih, Veni; Mahananto; Prasetyo, Agung (Journal of Rural and Urban Community Studies, 2025)
Organic rice cultivation is a cultivation using organic materials or natural materials that can be renewed as input so that products are produced that are free from chemicals that are harmful to health and ecosystem balance. While the pesticides used are botanical pesticides. The application of organic systems in addition to restoring the soil agro-ecosystem can also increase farm income. The purpose of this study was to determine the amount of income and costs of organic and non-organic rice farming with the same variety in Dukuh Village, Delanggu District. The analytical tools used were cost analysis, income analysis and t-test. The conclusion of the study can be concluded that the costs incurred by farmers for organic rice farming are greater than non-organic rice farming, but the income of organic farmers is greater than that of non-organic farmers. This is shown from the results of the calculation showing an average organic rice farming income of IDR 30,482,568.2 per hectare, while the farm income from the calculation results shows that the income of non-organic rice farming is IDR 21,114,381.9 per hectare. The results of statistical tests show a significant difference. Income from organic rice farming is greater than income from farming with a non-organic rice system.